2022
DOI: 10.1075/silv.28.03sta
|View full text |Cite
|
Sign up to set email alerts
|

Production and evaluation of sociolinguistic variation in Mandarin Chinese among children in Singapore

Abstract: Singapore Mandarin is traditionally characterized by non-standard features arising from southern Chinese dialect influence. However, as English expands as a home language in Singapore, children’s Mandarin exposure is increasingly limited to formal school settings. The situation is further complicated by rising immigration from Mainland China and the presence of Mainland teachers in the education sector. This study investigates how local an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…For instance, Chen et al, (2016) found that primary schoolaged children displayed more consistent use of the retroflex feature in their production of Mandarin speech as compared to older generations of Singapore Mandarin speakers. Similarly, using a word reading task, Starr (2022) found that only a minority of Singapore Mandarin speaking children produced retroflex sibilants as alveolar instead. This shift is likely related to the increase in the levels of exposure that young Singapore Mandarin speakers have to the standard variety of Mandarin in formal education (i.e., at school as well as in extracurricular language enrichment centres), and through mass media in standard Singapore and Mainland Mandarin (Starr & Kapoor, 2021).…”
Section: Current Literature Suggests That Mandarin Proficiency Amongstmentioning
confidence: 95%
See 4 more Smart Citations
“…For instance, Chen et al, (2016) found that primary schoolaged children displayed more consistent use of the retroflex feature in their production of Mandarin speech as compared to older generations of Singapore Mandarin speakers. Similarly, using a word reading task, Starr (2022) found that only a minority of Singapore Mandarin speaking children produced retroflex sibilants as alveolar instead. This shift is likely related to the increase in the levels of exposure that young Singapore Mandarin speakers have to the standard variety of Mandarin in formal education (i.e., at school as well as in extracurricular language enrichment centres), and through mass media in standard Singapore and Mainland Mandarin (Starr & Kapoor, 2021).…”
Section: Current Literature Suggests That Mandarin Proficiency Amongstmentioning
confidence: 95%
“…The intergenerational influence of this linguistic divide can still be seen in the 2020 census of Singapore which shows that 30% of ethnically Chinese residents report using Mandarin Chinese as their dominant home language, while 48% report using English as their dominant home language (DOS, 2021). Thus, it is likely that we will find a variety of (Starr, 2022). Similarly, it is also common for Singapore Mandarin speakers to produce Mandarin palatal frication /ɕ/ as the alveolar /s/ due to the lack of a palatal /ɕ/ in the phonology of Hokkien (Starr, 2022;Starr & Wang, 2021).…”
Section: Current Literature Suggests That Mandarin Proficiency Amongstmentioning
confidence: 99%
See 3 more Smart Citations